PERAN KONSTITUSI DALAM MEMPERKUAT INTEGRASI DI INDONESIA - Marisi Inrina Siahaan; Viona Elisa Sinambela; Halimah Tusya'diah Lubis; Windy Amanda Purba; Dewi Sari Arta Nababan; Suci Khayla; Cindi Veronika Tamba (JOURNAL SAINS STUDENT RESEARCH, 2024)
The constitution plays an important role in strengthening Indonesia's national integration. As the basic law of the state, the constitution establishes fundamental principles that unite the diverse nation. Some of the key roles of the constitution in promoting integration include: Affirming a shared national identity through Pancasila as the foundation of the state. Guaranteeing equal rights and obligations of all citizens without discrimination. Recognizing the diversity of ethnicities, religions, and cultures as national wealth. Establishing a system of government that balances central and regional power. Providing a legal framework for peaceful conflict resolution. Protecting the rights of minority groups and indigenous peoples. And promoting equitable development throughout Indonesia. With these roles, the Indonesian constitution is an important foundation for national unity amidst diversity. However, the implementation of constitutional values in national life still requires ongoing efforts from all elements of society.